Superoxide dismutase@zeolite Imidazolate Framework-8 Attenuates Noise-Induced Hearing Loss in Rats - Zhang, Yan; Li, Qing; Han, Chengzhou; Geng, Fang; Zhang, Sen; Qu, Yan; Tang, Wenxue (Frontiers in Pharmacology, 2022)
Reactive oxygen species (ROS) and inflammation have been considered major contributors to noise-induced hearing loss (NIHL) that constituted a public health threat worldwide. Nanoantioxidants, with high antioxidant activity and good stability, have been extensively used in the study of ROS-related diseases. In this study, we constructed a superoxide dismutase (SOD)@zeolite imidazolate framework-8 (ZIF-8) nanoparticle based on biomimetic mineralization and applied it to a rat model of NIHL. Our results showed that SOD@ZIF-8 effectively protected the animals from hearing loss and hair cell loss caused by noise. ROS, oxidative damage, and inflammation of noise-damaged cochlea were attenuated considerably after SOD@ZIF-8 administration. Importantly, we found that SOD@ZIF-8 achieved nanotherapy for NIHL in rats via a primary effect on the Sirtuin-3 (SIRT3)/superoxide dismutase2 (SOD2) signaling pathway without obvious adverse side effects. Therefore, our study is expected to open up a new field for NIHL treatment, and lay a foundation for the application of nanomaterials in other ROS-related inner ear diseases.